Cutaneous hyphomycosis Caused by Purpureocillium lilacinus Infection Associated with Superficial Venipuncture: A Case Report - Zhou L; Qi X; Guo G; Wang Y; Yang J; Yang D; Huang S (Dove Medical Press, 2023)
Lijun Zhou,* Xinyu Qi,* Guiying Guo, Yanling Wang, Jianjun Yang, Dingbin Yang, Shuqiong Huang Department of Dermatology, People's Hospital of Leshan, Leshan, Sichuan, 614000, People's Republic of China*These authors contributed equally to this workCorrespondence: Shuqiong Huang, Department of Dermatology, People's Hospital of Leshan, No. 238, Bai Ta Road, Shi Zhong Qu, Leshan, Sichuan, 614000, People's Republic of China, Email 793438717@qq.comAbstract: Cutaneous hyphomycosis caused by Purpureocillium lilacinus is a relatively uncommon event in patients, but there has been a gradual increase in reported cases. A 71-year-old female patient was hospitalized in May 2022 due to an acute episode of chronic obstructive pulmonary disease and received glucocorticoid infusion. The skin around the puncture point on the back of her right hand showed erythema, nodules, scabs, and pus discharge, which gradually worsened. Fungal examination revealed the presence of hyphae, while treatment with terbinafine was ineffective. After fungal culture, pathological analysis, and molecular biology identification techniques, this case was diagnosed as cutaneous and subcutaneous infections caused by Purpureocillium lilacinus. After 2 weeks of treatment with itraconazole, the patient recovered. Patients on long-term hormone preparations who undergo superficial venipuncture should be aware of the risk of skin damage and potential infection by Purpureocillium lilacinus. Prompt fungal culture, histopathological analysis, and molecular identification are crucial for accurate diagnosis. Antifungal susceptibility testing should be considered for effective treatment.Keywords: infection of Purpureocillium lilacinus, superficial venipuncture, a case report, infection